PERANAN ORANG TUA DALAM MEMBINA AKHLAK ANAK PADA MASA PUBERTAS DI JORONG TANGAH PADANG KAB. LIMA PULUH KOTA - Puspita Sari, Welly (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
The background of this research is the problem of the role of parents, namely the existence of parents who give freedom and tend to ignore the behavior and relationships of their children so that children have bad morals such as delaying prayer times, dating and fighting if advised by their parents. Therefore, the authors are interested in conducting research related to what are the roles and obstacles faced by parents in fostering children's morals during puberty in Jorong Tangah Padang, Kab. 50 Kota. In conducting this research, the writer uses field research with a qualitative approach, namely describing what is about a situation. The informants of this study were parents and children at puberty as key informants and Mr. Jorong as supporting informants. The data collection tool that the author uses is interviews. The data analysis technique that the author uses is data reduction, data display and data verification. Based on the results of the research and data analysis that the authors did, it can be concluded that in fostering morals parents have taken various ways such as guiding and directing children to carry out worship, giving examples to children about good morals, providing sex education, as well as advising and giving punishment if the child makes a mistake. However, it is the assistance and attention that have not been fully carried out by the parents. This is because parents are busy looking for sustenance and the social environment is also very influential on the formation of children's morals.